2014
DOI: 10.1097/jom.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Angiosarcoma of the Liver Among Vinyl Chloride Workers

Abstract: We may have seen the last case of ASL among workers exposed to vinyl chloride. Nevertheless, given the long latency of this cancer, continued surveillance seems prudent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Collins et al reported 15 cases of ASL in the most recent update of the Dow chemical company diseases registry for ASL [ 65 ]. Thirteen ASL cases were at a single plant with high VCM exposure before 1974, which could indicate that exposures were higher at this location than the other locations.…”
Section: Resultsmentioning
confidence: 99%
“…Collins et al reported 15 cases of ASL in the most recent update of the Dow chemical company diseases registry for ASL [ 65 ]. Thirteen ASL cases were at a single plant with high VCM exposure before 1974, which could indicate that exposures were higher at this location than the other locations.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor development proved to be associated with numerous environmental carcinogens, such as iatrogenic exposure to the radiocontrast agent Thorotrast (colloidal thorium dioxide), industrial exposure to vinyl chloride monomers, chronic exposure to arsenical compounds and exposure to pesticides, external radiation, and radium. Additionally, cyclophosphamide, urethane, diethylstilbestrol, the use of oral contraceptives, phenylhydrazine, iron, androgenic or anabolic steroids proved to be risk factors associated with HAS development[36,37].…”
Section: Hepatic Angiosarcomasmentioning
confidence: 99%
“…Four findings are helpful to make the differential diagnosis with HHS: (I) HHS is more frequent in men; (II) may be due, in up to 25% of patients, to environmental, toxic factors such as vinyl chloride, cyclophosphamide, thorium dioxide (Thorotrast) and arsenic; (III) HHS is more aggressive, as shown by the more frequently compromised liver function (lower albumin, elevated INR, anaemia and thrombocytopenia) and (IV) at histological level, by the loss of the typical hepatic lobular and portal landmarks (11,13,32,38). It is known that the delay between toxic exposure and HHS development may be extremely long (35 to 65 years) (39,40).…”
Section: Hehementioning
confidence: 99%
“…It is rarely seen in children (42,(61)(62)(63). HHS received much attention due to the association with many environmental carcinogens (Thorotrast, vinyl chloride monomer, radium, pesticides, external radiation, cyclophosphamide, arsenical compounds, use of androgenic/anabolic steroids and iron) (9,23,39,40). Most cases are sporadic.…”
Section: Hhsmentioning
confidence: 99%